In vitro and in vivo antimalarial activities of the ethanol extract of Erythrina sigmoidea stem bark used for the treatment of malaria in the Western Region of Cameroon - Jemimah Sandra, Tientcheu Noutong; Christelle Nadia, Noumedem Anangmo; Cedric, Yamssi; Guy-Armand, Gamago Nkadeu; Azizi, Mounvera Abdel; Aboubakar Sidiki, Ngouyamsa Nsapkain; Alex Kevin, Tako Djimefo; Payne, Vincent Khan; Hu, Haibo (Frontiers in Parasitology, 2024)
Background: Malaria is one of the leading causes of morbidity and/or mortality in tropical Africa. The spread and development of resistance to chemical antimalarial drugs thus as the relatively high cost of the latter are problems associated with malaria control and are reason to promote the use of plants to meet health care needs to treat malaria. The aim of this study was to evaluate antiplasmodial activities of extracts of Erythrina sigmoidea (Mah quat) which is traditionally used for treatment of malaria in the Western Region of Cameroon.The aqueous extract had an in vitro antiplasmodial activity against the Chloroquinesensitive strain with an IC50 of 29.51±3.63 µg/mL and against the Chloroquine-resistant strain with an IC50 of 35.23±3.17 µg/mL. The highest in vitro antiplasmodial activity was observed with the ethanol extract against the Chloroquine-sensitive strain with an IC50 of 6.44±0.08 µg/mL and against the Chloroquine-resistant strain with an IC50 of 7.53±0.22 µg/mL. The ethanol extract demonstrated suppressive activity in vivo with reduction rates of 87.69%, 86.79% and 81.08% at doses of 500mg/kg, 250mg/kg and 125mg/kg respectively; and curative activity in vivo with reduction rates of 80%, 78.5%, and 77.5% at doses of 500mg/kg, 250mg/kg, and 125mg/kg respectively. The number of white blood cells in the negative control (44.55±5.02 10 3 /µL) was higher compared to the other groups. As for the red blood cells, we observed a massive destruction of the latter in the infected and untreated group (5.82±1.50 10 6 /µL) compared to the infected and ethanol extract treated groups (8.74±1.57 10 6 /µL for 500mg/kg, 7.54±1.77 10 6 /µL for 250mg/kg, and 8.9±1.50 10 6 /µL for 125mg/kg).This study provides scientific data on the use of Erythrina sigmoidea by the local population for the treatment of malaria. It shows that E. sigmoidea has antiplasmodial activity and we also see that there are differences between the parameters that we have in the treated groups and those of the untreated group. However, toxicity tests are necessary to assess its safety